Phenomenology of cosmic ray transport in the galaxy - Batista, Pedro Ivo Silva (2019)
In this dissertation we provide new benchmark scenarios for galactic cosmic ray propagation in view of the recent precise measurements of the Boron to Carbon flux ratio from the Alpha Magnetic Spectrometer (AMS-02), based on fits to data using the USINE code. We identify a general scenario that provides excellent fits to the data and includes all relevant physical processes, the BIG model. This model has two limiting regimes: the SLIM model, which is characterised by a minimal diffusion-only description, as well as the QUAINT model, with reacceleration and convection. Moreover, we present a study of the spectral index of the B/C ratio, aiming at understanding the differences between this observable and the diffusion coefficient spectral index, showing that these two quantities are not interchangeable. We generalize our analysis to all CR nuclei, from H to Fe, and compare to existing AMS-02 measurements.